From marks to profiles and "records of achievement" - Withers, Graeme (Geelong, Vic. : Deakin University : distributed by Deakin University Press, 1991)
Introduction. The assessment background. Recording. Reporting. Two case studies.
Keywords: Education; Educational tests and measurements